Species diversity pattern and its drivers of the understory herbaceous plants in a Chinese subtropical forest - Tian, Kai; Chai, Pengtao; Wang, Yunquan; Chen, Lei; Qian, Haiyuan; Chen, Shengwen; Mi, Xiangcheng; Ren, Haibao; Ma, Keping; Chen, Jianhua (Frontiers in Ecology and Evolution, 2023)
Understory herbaceous plants are an important component of forest ecosystems, playing important roles in species diversity and forest dynamics in forests. However, the current understanding of biodiversity of forest communities are mostly from woody plants, knowledge of community structure and species diversity for understory herbaceous plants remains scarce. In a subtropical forest in China, we investigated understory vascular herbaceous diversity from 300 plots (5 m × 5 m) in the main growing season. Here, we analyzed the community structure and diversity pattern of understory herbaceous community, and linked the species diversity pattern to both abiotic and biotic environments. We found a rich diversity of understory herbaceous communities in this forest (81 species belonging to 55 genera), and floristic elements at genus level were dominated by tropical elements, followed by temperate elements. The diversity pattern of understory herbaceous showed a significant habitat preference, with highest diversity in the lowland valleys and then followed by in middle slopes. In addition, herbaceous diversity was significantly affected by both abiotic factors (such as terrain convexity) and biotic factors (such as diversity of surrounding woody plants). Our study indicated that species diversity of understory herbaceous shown a remarkable habitat preference such as lowland valleys, and highlight the importance of both abiotic and biotic environments in driving herbaceous diversity pattern in the subtropical forest understory.